Functional dissection of the phosphorylated termini of fission yeast DNA topoisomerase II (The Rockefeller University Press, 1992)
Fission Yeast DNA topoisomerase II (165 kD) consists of an enzymatically active 125-kD core, approximately 10-kD NH2-terminal and 30-kD COOH-terminal domains. The question addressed in the present study is what is the role of the topo II termini. Although deletion of either the NH2 or the COOH terminus is viable, deletion of both termini is lethal; the termini share an essential role for viability. We show here that topo II phosphorylation sites are localized in the terminal domains, but dephosphorylated topo II is still active. The topo II terminal sequences are required for nuclear localization; topo II double terminal deletion mutants are deficient for nuclear targeting, whereas wild-type and single deletion mutant topo IIs are transported into the nucleus with different efficiencies. Functional subdomains in the NH2 terminus are further dissected; we identified a 15 amino acid nuclear localization sequence (NLS) which is essential for viability and nuclear localization when the COOH terminus is deleted. This NLS could be substituted with SV-40 large T-antigen NLS. Two other functional subdomains were found; a non-essential acidic stretch which is phosphorylated and apparently enhances the nuclear localization and an essential hydrophilic stretch of unknown function. Motifs similar to these three NH2-terminal subdomains are also found in the COOH terminus. Our results support the possibility that phosphorylation of topo II does not play an essential role in fission yeast.